Hubungan Antara Pola Asuh Orang Tua dengan Temper Tantrum Anak Autis di SLB AGCA Center Surakarta - Rizal Dwi Yuliandika; Dewi Suryandari (Jurnal Berita Ilmu Keperawatan, 2019)
Growth and development, especially in children, sometimes impaired either before birth or after birth. Developmental disorders in children one of which is a developmental disorder behavior. Autism is one of irregularities in development since infancy. The purpose of this study was to determine the description of parents' parenting autistic children in SLB Agca Center Surakarta and analyze the relationship between foster parents with autistic children in special schools tantrums Agca Center Surakarta. The result is expected to increase the knowledge and contribute to the parties involved in this research about the types of parenting parents the right to their children, especially to children dishabilitas, such as autistic children. This study design using correlational, which examines the relationship between variables. Method is a cross sectional approach. The population in this study are all autistic children in SLB Agca Center Surakarta numbered 34 children. The sample in this study were students with autism SLB Agca Center Surakarta totaling 34 children. The sampling technique used is total sampling. Analysis of the data in this study using univariate and bivariate analysis aimed to test the hypothesis or testing a relationship between parenting parents with an autistic child temper tantrums in SLB Agca Center Surakarta. The results showed that parents' parenting of children autism in SLB Agca Center Surakarta included in the category of good, and the trend parenting democratic show that autistic children at SLB Agca Center Surakarta has temper tantrums low and temper tantrums of children autism in SLB Agca Center Surakarta included in the category are low, this indicates that the planting of education in SLB Agca Center Surakarta quite successful. There is a correlation between parenting system and temper tantrum of children with Autism Syndrom Disorder in Agca Center Surakarta.